Current concept of the diagnostics and treatment of vulvovaginal candidosis - YE. T. Malbakhova; V. G. Arzumanyan (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
In spite of high prevalence of vulvovaginal candidosis (VVC), its diagnostics and treatment pose a serious problem. Factors such as accessibility of antimycotic drugs, their uncontrolled application by patients and absence of any appropriate laboratory diagnostics result in the growth of the incidence rate, in particular, of recurrent forms related to a steady growth in the number of fungi of clinical importance as well as strains resistant to antifungal drugs. Discussion and conclusion. Today the problem of the need to develop VVC prevention drugs is increasingly urgent because reduced immunity results in relapses of the disease. Clinical trials of drugs for immune system correction are ongoing, and some of them have reached Phase 2. Based on the present-day research data, it is possible to conclude that the key standards for VVC diagnostics and treatment are as follows: mandatory diagnostics with the use of microbiological tests to determine the sensitivity to antifungal medicines, in particular, in case of recurrent VVC, and collection of detailed medical history data and physical examination to determine the form and severity of the disease (acute, recurrent, complicated or uncomplicated) and treatment duration: 1-7 days for acute uncomplicated forms and 7-14 days for recurrent complicated forms. The specific drug and route of administration are to be selected based on the physician's preferences, patient's convenience and cost of the drug provided the drug sensitivity is determined by laboratory tests. The administration of probiotics for VVC prevention and treatment is disputable today.